Green building management and smart automation - Solanki, Arun, 1985-; Nayyar, Anand (Engineering Science Reference, an imprint of IGI Global, 2020)
"This book examines smart automation technologies which assist in energy conservation along with various performance metrics which are necessary to facilitate a building to be known as a 'green smart building'"--